Behavioral science in the global arena : addressing timely issues at the United Nations and beyond - Congress, Elaine Piller; Takooshian, Harold; Asper, Abigail (Charlotte, NC : Information Age Publishing, Inc., 2020)
"Behavioral scientists are increasingly involved in international work through cross cultural research, conference presentations, and faculty exchanges. Psychology and social work NGOs work at the United Nations, both on providing professional consultation on timely issues, as well as advocating to promote human rights and sustainable development. Although this work at the United Nations is an important arena for behavioral scientists, this has been barely covered in the academic literature"--
Includes bibliographical references.
Keywords: United Nations; Psychology -- Social aspects; Social policy -- Psychological aspects; Social policy -- International cooperation; International cooperation -- Psychological aspects